The putative actin-binding role of hydrophobic residues Trp546 and Phe547 in chicken gizzard heavy meromyosin. - Onishi, H (1995)
In the course of myosin-catalyzed ATP hydrolysis, certain amino acid residues in myosin interact with counterparts in actin to produce the relational changes that underlie muscle contraction; some of these interactions are ionic, but the stronger interactions are hydrophobic. In an effort to identify myosin residues participating in hydrophobic interactions, myosin (from smooth muscle) fragments with mutations at suspected sites were engineered and compared with wild-type fragments. It was found that the ATPase of doubly mutated (Trp546Ser and Phe547His) fragments was minimally activated by actin and did not decorate actin well to form the regular arrowhead pattern characteristic of myosin binding to actin filaments. Thus, we suggest that Trp546 and Phe547 are important participants in the hydrophobic actin-myosin interaction.